Advances in biomarkers for optic neuritis and neuromyelitis optica spectrum disorders: a multi-omics perspective - Liu, Lidong; Guo, Kai; Yang, Dayong (Frontiers in Neurology, 2025)
Optic neuritis (ON) and neuromyelitis optica spectrum disorders (NMOSD) are inflammatory neuro-ophthalmological conditions characterized by significant visual impairment and diverse clinical manifestations. Advances in diagnostic biomarkers have improved disease identification, including aquaporin-4 immunoglobulin G (AQP4-IgG) and myelin oligodendrocyte glycoprotein immunoglobulin G (MOG-IgG). However, some patients remain biomarker-negative, complicating differential diagnosis and personalized treatment. Multi-omics approaches have provided valuable insights into critical molecular pathways, novel biomarkers, and the shared and distinct features of ON and NMOSD. This review highlights recent advancements in biomarker research for ON and NMOSD, emphasizes the potential of multi-omics integration, identifies existing challenges, and proposes future research directions. These findings aim to enhance diagnostic accuracy, improve prognostic capabilities, and support the development of precision medicine strategies for ON and NMOSD.